Tanggung jawab sosial PT.Chevron Pasifik Indonesia di Provinsi Riau untuk pembangunan berkelanjutan - Afrizal Afrizal; Sujianto Sujianto; Zulkarnain Zulkarnain; Firdaus Firdaus (Universitas Riau, 2021)
Sustainable development is development that pays attention to the three main aspects; they are economy, social and environment aspects. Riau Province is one of the province that have great quantities of corporate, either foreign or local corporate. Sustainable corporate social responsibility in this province, is obligated by district regulation, no. 6, 2012. The development of companies in Riau Province increased in the oil and natural gas, plantation, forestry and mining sectors. The existence of the company give positive impact such as the raising of the economics matter and increasing the local income by the responsibility fell on the economic, social and environment condition where the company operate. The purpose of this research is: to study how is the responsibility of CPI Ltd. In Riau Province in the effort to support economy, social and sustainable development. The method used in this research is the use of descriptive qualitative method. Qualitative method is used for describing the authentic relationship between variables in the research problem empirically by the big amount of simultaneous influence sharpening together and toward value pattern be faced. CSR program done in Riau Province is the program in social, economics and environmental program. The CSR become the effort to support sustainable development because the advantages can be felt by the society for today and future